Social interaction of coaches and parents increases the motivation of adolescent swimming athletes - Aliya, Rusyda Nur; Nurjaya, Dede Rohmat; Kardjono, Kardjono; Komarudin, Komarudin; Novian, Geraldi (Jurnal Ilmu Keolahragaan, 2025)
Background. The reason for this study is the mismatch between theory and reality in the field, where social support from parents and coaches which should tend to be positive in increasing athlete motivation, in practice can actually become pressure and cause stress and loss of motivation. Objectives. This research addresses the understanding of how social interactions between coaches and parents influence the motivation of adolescent swimming athletes. The purpose of this study, to determine the effect of social interactions of coaches and parents on the motivation of adolescent swimming athletes. Methods. The method used in this research is descriptive method with quantitative approach. The population used was Samudra Swimming Club swimming athletes, the sample of athletes taken was 30 athletes according to the Age Category (KU) of adolescents 10-17 years taken through purposive sampling. This study used an instrument in the form of a questionnaire "Motivation to Learn Achievement." Data analysis was done with paired sample T-test. Results. The results showed that the social interaction of coaches and parents had a significant influence on the motivation of adolescent swimming athletes aged 10-17 years at Samudra Swimming Club. The conclusion of this study shows that 58% of athletes are in the moderately mastering category.. Conclusion. This indicates that most athletes feel motivated in swimming lessons thanks to the guidance of coaches and the support of parents who play a role in social interactions to increase their motivation as swimming athletes at Samudra Swimming Club. This study recommends the active role of coaches and parents in supporting the motivation of adolescent swimming athletes.